Comparación de métodos moleculares y serológicos en el diagnóstico de la viruela símica - Carrazco Flores, Johanna Lizbeth (2025)
Monkeypox is an infectious disease caused by the Mpox virus. The incidence of Mpox during the 2022 outbreak was 96.8%, with 23.08% of cases reported in Africa, and the median age being 34 years. Molecular and serological methods are the most commonly used tests to diagnose Mpox, based on these premises, this research aims to compare the efficacy and efficiency of various molecular and serological methods used to diagnose Mpox through a systematic literature review. The study used the PICO question strategy with Boolean operators and the PRISMA methodology for development. Twenty scientific articles were found, evidencing the reliability of molecular and serological methods in diagnosing Monkeypox. Various molecular methods, including real-time PCR, RT-PCR, dPCR, QPCR, and genetic sequencing, and serological methods like multi-antigen ELISA, viral antigen identification, and neutralization tests, were described and evaluated for their efficacy and efficiency. Molecular methods are most commonly used due to their sensitivity and specificity, providing quick, accurate, and effective diagnosis.